Storage Technique Socialization Ingredient Food to be Long Lasting and Content Nutrition Permanent Awake - Anida Ihdal Husnayayyin (Universitas Pendidikan Indonesia, 2023)
This research was carried out with the aim of knowing the effect of socialization on increasing public understanding of the importance of storing food ingredients properly to keep them nutritious and durable. The method used is descriptive qualitative with data collection techniques through questionnaires filled out by 19 respondents who are residents of Cigugurgirang, Parongpong, Indonesia. The stages of data collection carried out are as follows; (1) pre-test, (2) socialization through learning media in the form of PowerPoint, and (3) post-test addressed to respondents. The results of the questionnaire data analysis, it can be seen that the provision of material through PowerPoint media given to respondents tends to have a positive impact. This can be seen through the answers in the post-test which have increased in a positive direction compared to the answers at the pretest. This research through the socialization of food storage techniques so they are durable and nutritional content is maintained is expected to educate the community in the Cigugurgirang area in paying attention to food safety in food processing and storage so the nutritional content is maintained.